Relationship between public mental health stigma, mental health literacy, and help-seeking behaviour among adults in Malaysia - Chan, Ming Chen; Chew, Jia Xin; Soh, Lilian Li-Ern (2024)
In recent years following the post-COVID period, the number of individuals suffering from mental health issues continue to accumulate despite the notable increase in awareness regarding mental health. The often cause related to this issue of low levels in help-seeking behaviours would usually be the presence of stigma from the public with regards to mental health, and also mental health literacy (MHL). The present study examined the association linking the presence of public mental health stigma (PMHS) and mental health literacy (MHL) with help-seeking behaviours among adults in Malaysia. Correlational cross-sectional research design was utilised in this current research whereby self-reported data was collected among Malaysian adults. A final total of 179 samples (Mage = 28.28, SDage = 13.158) was gathered by using purposive sampling method. The majority of the participants were females (72.6%). As for the ethnicity of the respondents, the majority were Chinese (97.2%), followed by Indians (1.7%), and others (1.1%). Results have indicated significant relationships between the two predictors, PMHS and MHL, and help-seeking behaviour with negative and positive correlation for each respectively. The current study is therefore helpful in attempts to fill the gap in literature available for the Malaysian context, where cultural and social factors are contemplated. Practical implications were also a result of the study, urging the government to act in accordance with the objectives in the implemented plans for mental health, and for relevant parties to heed to the efforts by the government. This can be done by educating themselves and others in order to minimize the stigma surrounding topics of mental health and help-seeking.